Chinese validation of the Rasch‐Built Overall Amyotrophic Lateral Sclerosis Disability Scale. (27th March 2021) - Sun, Can; Fournier, Christina N.; Ye, Shan; Zhang, Nan; Ma, Yan; Fan, Dongsheng
Abstract: Background and purpose: The Rasch‐Built Overall Amyotrophic Lateral Sclerosis Disability Scale (ROADS) was developed using Rasch methodology. This scale has been demonstrated as a reliable outcome measure of amyotrophic lateral sclerosis (ALS) trials. To date, there are no similar interval‐weighted scales to assess disability in ALS patients. The current study aimed to validate a Chinese version of the ROADS via Rasch methodology. Methods: The Chinese version of the ROADS was obtained through a standardized forward–backward translation and cultural adaptation. ALS patients were recruited from the Department of Neurology of Peking University Third Hospital in Beijing, China to complete the ROADS and the revised ALS Functional Rating Scale (ALSFRS‐R). Overall, 254 participants with ALS finished the Chinese scale. Rasch analysis was performed on the ROADS for validation and the ALSFRS‐R for comparison. Results: The Chinese version of the ROADS was modified according to the statistical results. A final 28‐question scale was constructed that fulfilled all the requirements of the Rasch model with proper validity and reliability. Furthermore, the ROADS showed improved item targeting compared to the ALSFRS‐R. Conversely, the ALSFRS‐R did not fit the Rasch model expectations due to misfit values and disordered thresholds for all 12 items. Conclusions: The Chinese adaptation of the ROADS is a linearly weighted scale that specifically captures overall disability in ALS patients. This scale indicates a wider range of item difficulties and better responsiveness than the ALSFRS‐R. The ROADS could be used as a valuable tool for use in ALS trials and in the clinic in Chinese settings. Abstract : The Chinese version of the Rasch‐Built Overall Amyotrophic Lateral Sclerosis Disability Scale (ROADS) was validated by Rasch analysis with proper validity and reliability. It indicates a wider range of item difficulties and better responsiveness than the revised Amyotrophic Lateral Sclerosis Functional Rating Scale. The ROADS could be used as a valuable tool for use in amyotrophic lateral sclerosis trials and in the clinic in Chinese settings.